PENGARUH IKLAN TELEVISI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MIE INSTAN (SURVEI PADA MASYARAKAT TANJUNG SELAMAT) - Ritonga, Zuriani (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2018)
This research was to know: (1) the influence of television commercials against the decision of the purchase of instant noodles (survey with the community of Tanjung selamat), (2) the influence of the price of the purchase decision instant noodles (survey with the community of Tanjung selamat). This research including survey research with quantitative approach. The population in this research is the community of Tanjung Selamat. Based on the results of the calculation of the specified number of samples is used as much as 98 people. Data collection techniques using questionnaires that have been tested and reliabilitasnya validity. Data analysis technique that is used is a double linier regression. The results of the study showed that: (1) influential television commercials significant on the Tanjung Selamat, proved from the value of the significance of 0,000<0.05 and regression coefficient of 0,058, (2) the price of a significant effect of Tanjung Selamat, proved from the significance of 0,000<0.05 and regression coefficient of 0,181.